The Proximity of Ribosomal Protein Genes to oriC Enhances Vibrio cholerae Fitness in the Absence of Multifork Replication - Alfonso Soler-Bistué (American Society for Microbiology, 2017)
ABSTRACT Recent works suggest that bacterial gene order links chromosome structure to cell homeostasis. Comparative genomics showed that, in fast-growing bacteria, ribosomal protein genes (RP) locate near the replication origin (oriC). We recently showed that Vibrio cholerae employs this positional bias as a growth optimization strategy: under fast-growth conditions, multifork replication increases RP dosage and expression. However, RP location may provide advantages in a dosage-independent manner: for example, the physical proximity of the many ribosomal components, in the context of a crowded cytoplasm, may favor ribosome biogenesis. To uncover putative dosage-independent effects, we studied isogenic V. cholerae derivatives in which the major RP locus, S10-spc-α (S10), was relocated to alternative genomic positions. When bacteria grew fast, bacterial fitness was reduced according to the S10 relative distance to oriC. The growth of wild-type V. cholerae could not be improved by additional copies of the locus, suggesting a physiologically optimized genomic location. Slow growth is expected to uncouple RP position from dosage, since multifork replication does not occur. Under these conditions, we detected a fitness impairment when S10 was far from oriC. Deep sequencing followed by marker frequency analysis in the absence of multifork replication revealed an up to 30% S10 dosage reduction associated with its relocation that closely correlated with fitness alterations. Hence, the impact of S10 location goes beyond a growth optimization strategy during feast periods. RP location may be important during the whole life cycle of this pathogen. IMPORTANCE The role of gene order within the bacterial chromosome is poorly understood. In fast growers, the location of genes linked with the expression of genetic information (i.e., transcription and translation) is biased toward oriC. It was proposed that the location of these genes helps to maximize their expression by recruiting multifork replication during fast growth. Our results show that such genomic positioning impacts cell fitness beyond fast-growth conditions, probably across the whole life cycle of fast growers. Thus, the genomic position of key highly expressed genes, such as RP, was finely tuned during the evolution of fast-growing bacteria and may also be important in slow growers. In the near future, many more genes whose genomic position impacts bacterial phenotype will be described. These studies will contribute to discovery the rules of genome organization and application of them for the design of synthetic chromosomes and the creation of artificial life forms.